2023
DOI: 10.3389/fcomm.2023.1096639
|View full text |Cite|
|
Sign up to set email alerts
|

Transcribing and translating forensic speech evidence containing foreign languages—An Australian perspective

Abstract: There is a growing body of literature on forensic transcription of covert recordings obtained by clandestine law enforcement operations. Due to the nature of these operations, the quality of the recordings, particularly those obtained by planting listening devices in a car or a house, is often extremely poor. When tendering such recordings as evidence in court for prosecuting an alleged crime, a transcript will often accompany the recording to assist the triers of fact (i.e., judges and jurors) to hear better.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The High Courts of the state trust that the legal transcription service is free of abuses, but the legal transcription practices in the judicial system indicated that language use problems could potentially lead to distortion of the contents of evidences as proven by the studies of Buscholtz (2000), Richardson et al (2022), Fraser (2022) and Lai (2023). Law professionals, particularly judges, do not seem to have clear understanding of the linguistic process of transferring information from one language into another which is involved in the inter-lingual transcription, and the burden it creates on the individuals who perform legal transcription with no qualification for this language-related job.…”
Section: Discussionmentioning
confidence: 99%
“…The High Courts of the state trust that the legal transcription service is free of abuses, but the legal transcription practices in the judicial system indicated that language use problems could potentially lead to distortion of the contents of evidences as proven by the studies of Buscholtz (2000), Richardson et al (2022), Fraser (2022) and Lai (2023). Law professionals, particularly judges, do not seem to have clear understanding of the linguistic process of transferring information from one language into another which is involved in the inter-lingual transcription, and the burden it creates on the individuals who perform legal transcription with no qualification for this language-related job.…”
Section: Discussionmentioning
confidence: 99%